Simple Microwave Method for Detecting Water Holdup - Sheikh, S. I. (2008)
A microwave sensor is designed to measure the resonance behavior of the hydrocarbon mixture to determine the water holdup of a near horizontal oil carrying pipeline. This technique is particularly useful for detecting very small water holdup (<5%) as demonstrated by simulated and experimental results.